An analysis of surface water from an informal settlement, Langrug, Franschhoek: down a slippery slope - Fell, Jessica (Department of Environmental and Geographical Science, 2018)
Contaminated surface water from limited sanitation and drainage systems in informal settlements degrades receiving rivers. However, little is known about the water quality and flow of rivers draining informally settled catchments. This study explores the dynamics of a human water system in an informally settled catchment in the present, and then uses these insights to investigate possible trajectories in the future. The objectives are twofold: (i) to characterise the water quality and flow of a river draining an informally settled catchment in Franschhoek, South Africa, and, (ii) to investigate the hydrologic and water quality effects of future land use and climate changes in the catchment. River water samples were collected during dry days for four months and over five rainfall events. Highly elevated concentrations of NH₃-N (8.4 ± 5.2mg/L), PO₄³⁻ (5.9 ± 7.4mg/L) and TSS (135 ± 124mg/L) were recorded in the informal settlement. Correlation analyses between land use types and water quality showed significant relationships between informal settlement and NH₃-N, PO₄³⁻, DO, EC and TSS. Multiple regression models investigated six hypothetical land use changes scenarios and indicated that if informal settlement and built-up area doubled in size, there would be an increase in the concentration of NH₃-N by 83%, PO₄³⁻ by 85% and TSS by 86%. During the rainfall events multiple NH₃-N, PO₄³⁻, TSS concentration peaks were observed, with concentrations peaking at 3.5mg/L, 6.6mg/L and 1868mg/L respectively. Various significant correlations between lagged rainfall and pollutant concentrations revealed that rainfall caused an increase in NH₃-N, PO₄³⁻ and TSS after one hour, while NO₃⁻-N and DO responded to rainfall after two hours and flow after three hours. Multiple regression models explored two hypothetical climate change scenarios involving an increase in the 10 and 20 year design rainfall depth. The models demonstrated that if the rainfall depth of a 20 year rainfall event increased by 15%, there would be an increase in peak concentration of NH₃-N by 17% and PO₄³⁻ by 15%, a decrease in DO by 21%, and an increase in peak flow by 21%. The results reveal the pervasive impacts of the informal settlement on river water quality, especially as regards nutrient contamination from wastewater. The land use and climate change scenarios serve as a warning of the long term consequences of inevitable land use and climate changes in informal settlements.